ANALISIS PERJANJIAN KREDIT USAHA KECIL ANTARA BANK DAN PENGUSAHA - Marindowati, Marindowati (Lampung University)
Common business activities carried out by the bank for investments under its management, including various types of loans, among others. Investments in the form of credit is the main activity of a bank, because most of the income comes from lending banks. Provision of credit facilities by banks will help entrepreneurs in developing and improving their business, which in turn is expected to boost national economic growth.Keywords: Credit Agreement, Small Business